Mitochondrial Oxygen Monitoring During Surgical Repair of Congenital Diaphragmatic Hernia or Esophageal Atresia: A Feasibility Study - Costerus, Sophie A.; Bettink, Mark Wefers; Tibboel, Dick; de Graaff, Jurgen C.; Mik, Egbert G. (Frontiers in Pediatrics, 2020)
Current monitoring techniques in neonates lack sensitivity for hypoxia at cellular level. The recent introduction of the non-invasive Cellular Oxygen METabolism (COMET) monitor enables measuring in vivo mitochondrial oxygen tension(mitoPO2), based on oxygen-dependent quenching of delayed fluorescence of 5-aminolevulinic acid (ALA)-enhanced protoporphyrin IX. The aim is to determine the feasibility and safety of non-invasive mitoPO2 monitoring in surgical newborns. MitoPO2 measurements were conducted in a tertiary pediatric center during surgical repair of congenital diaphragmatic hernia or esophageal atresia. Intraoperative mitoPO2 monitoring was performed with a COMET monitor in 11 congenital diaphragmatic hernia and 4 esophageal atresia neonates with the median age at surgery being 2 days(IQR 1.25-5.75). Measurements were done at the skin and oxygen-dependent delayed fluorescence was measurable after at least 4 hours application of an ALA plaster. Pathophysiological disturbances led to perturbations in mitoPO2 and were not observed with standard monitoring modalities. The technique did not cause damage to the skin, and seemed safe in this respect in all patients, and in twelve cases intraoperative monitoring was successfully completed. Some external and potentially preventable factors – the measurement site being exposed to the disinfectant chlorohexidine, purple skin marker or infrared light - seemed responsible for the inability to detect an adequate delayed fluorescence signal. In conclusion, this is the first study showing it is possible to measure mitoPO2 in neonates and that the cutaneous administration of ALA to neonates in the described situation is safe. Preliminary data suggests that mitoPO2 in neonates responds to perturbations in physiological status.